Target culture teaching in the English as a second/foreign language classroom - Mohideen, Haja; Mohideen, Shamimah (KY Publications, India, 2016)
Culture learning leads to awareness of cultural practices in both individualistic and collectivist societies. To withstand culture shock, L2 learners need to be exposed to the L1 culture with the help of illustrations, dialogues, etc. A grade 10 textbook is used to demonstrate linguocultural teaching which advocates teaching of target culture alongside the materials used in the classroom. Cultural knowledge has even come to be described as the fifth language skill. Knowledge of culture sensitivity is part of sociolinguistic competence.